Potret masyarakat urban dalam novel Teman Tapi Menikah karya Ayudia Bing Slamet dan Ditto Percussion - Pandanwangi, Wiekandini Dyah; Setyaningtyas, Siwi Annisa; Yanti, Sri Nani Hari (Universitas Mulawarman, 2025)
This research analyses the lifestyle of urban society in the novel Teman Tapi Menikah by Ayudia Bing Slamet and Ditto Percussion. The background of the research is the dynamics of modern life reflected by urban society in the novel. This research aims to analyze the lifestyle of urban communities in novels relevant to the lives of people in big cities today. The method used is a qualitative description with a Sociology of Literature approach. Data collection is done by literature study through reading and note-taking techniques. Data analysis uses content analysis techniques or content analysis by the research problem. The results showed five lifestyles of urban society in the novel Teman Tapi Menikah, namely individualist lifestyle, instant lifestyle, recreational or entertainment lifestyle, virtual lifestyle, and mobility lifestyle. The implication of the research results is that the novel Teman Tapi Menikah is a social criticism of the lives of urban people in big cities who have lost their families and mutual cooperation. In addition, it criticizes that people today do not like the process, so they become people who are easily discouraged and not resilient.